1997
DOI: 10.1177/107110079701800906
|View full text |Cite
|
Sign up to set email alerts
|

Etiology, Histopathology, and Outcome of Surgery in Achillodynia

Abstract: Fifty-eight patients suffering from achillodynia for a median of 12 months (range, 4-240 months) were analyzed using history, clinical findings, ultrasound findings, histopathology, and surgical outcome. Surgical criteria were daily pain or inability to perform sports activity and failure of nonoperative treatment. There were 34 men and 24 women, 31% (18 of 58 patients) of whom had no direct association with sports or vigorous physical activity. Ultrasonography was performed in all cases and showed low echogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
184
0
8

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(194 citation statements)
references
References 19 publications
2
184
0
8
Order By: Relevance
“…Stanish and co-workers (2000) devised a system for tendon symptom classification (Table 4). To our knowledge, this classification system has not been evaluated for reliability and validity, but it has been used as an outcome measure after surgery in patients who have achillodynia (Rolf and Movin, 1997). Table 4.…”
Section: Outcome Scores -Questionnairementioning
confidence: 99%
See 1 more Smart Citation
“…Stanish and co-workers (2000) devised a system for tendon symptom classification (Table 4). To our knowledge, this classification system has not been evaluated for reliability and validity, but it has been used as an outcome measure after surgery in patients who have achillodynia (Rolf and Movin, 1997). Table 4.…”
Section: Outcome Scores -Questionnairementioning
confidence: 99%
“…Achilles tendinopathy is, however, not always related to excessive physical activity. It has been found that about one third of patients with Achilles tendinopathy do not participate in vigorous physical activity (Rolf and Movin, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…45,59 The less active are not immune as a minority of cases have been reported in sedentary groups. 43,107 Although runners appear to be the most commonly affected cohort, 59,60,62,98 Achilles disorders have been reported in a wide variety of sports. 32,33,59,60,134 It was noted that athletes are more likely to become symptomatic when training as opposed to during competitive events.…”
Section: Prevalencementioning
confidence: 99%
“…It is not always associated with excessive physical activity, and in a series of 58 patients, 31% did not participate in sports or vigorous physical activity [10] . Furthermore, the use of some drugs is associated with Achilles tendinopathy and rupture [11][12][13] .…”
Section: Introductionmentioning
confidence: 99%